Analysis of the Impact of Instilling Religious Moderation on Students' Social Attitudes - Sarno Hanipudin; Nur Alizatul Nasihah; Taqiyudin Subki (PT. Islamic Research Publisher, 2023)
The research is motivated by the implementation of instilling the values of religious moderation in students through Islamic Religious Education (PAI) learning, aiming to foster positive attitudes among students towards the diverse religious landscape in Indonesia. PAI teaching involves instilling several values of religious moderation, including tolerance, morality, consultation, nationalism, equality, and equity. The diversity present in Indonesia is considered a blessing that should be preserved and cherished, thus emphasizing the need for unity among different religious, ethnic, cultural, and traditional groups. The implementation of religious moderation values serves as an appropriate strategy to promote harmony and peaceful coexistence amidst the existing differences. The research is conducted at Yos Sudarso Majenang High School, an educational institution affiliated with the Catholic Church, despite having a majority of Muslim students. This study adopts a field research approach, employing a qualitative descriptive method. Data collection methods include interviews, observations, and documentation.